Respuesta :
On the left side use distributive property:
3(n) + (3)(4) = -6 + 15n
3n + 12 = -6 + 15n
Subtract 3n:
12 = -6 + 12n
Add 6:
18 = 12n
Divide 12:
18/12 = n
You can simplify it further:
n = 3/2 or 1.5
3(n) + (3)(4) = -6 + 15n
3n + 12 = -6 + 15n
Subtract 3n:
12 = -6 + 12n
Add 6:
18 = 12n
Divide 12:
18/12 = n
You can simplify it further:
n = 3/2 or 1.5
To solve for n, you need to do the numbers in parentheses first. 3(n+4) = 3n + 12. Add 6 to both sides of the equation, so now you have: 3n+18=15n. Subtract 3n from both sides, which isolates n to one side of the equation. You now have 18 = 12n. Divide both sides by 12, which will give you 1.5 = n.